1989
DOI: 10.1039/dc9898700263
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of CO on stepped and non-stepped surfaces of transition metals

Abstract: Results of extended Huckel calculations show that coordination of CO to Group VIII transition-metal surfaces depends on a subtle balance of the interaction with the CO 5cr orbital, that tends to direct the CO molecule to the atop position and the CO 2 7 ~" orbital, that directs the molecule to higher coordination sites. In the atop position, the changes in bonding to different surfaces of the same metal can be mainly attributed to differences in the interaction with the CO SCT molecular orbital. The favoured d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…We argued in section 2 that changes of the interaction of the CO 5u, a.nd the surface metal d orbitals dominate coordination of CO to Pt. The analysis presented here not only agrees with this, it also predicts that CO binds most strongly atop to the (111) surface (7). Only at lower d-valence electron occupation coordination to the more open surfaces becomes favoured.…”
Section: As Mentioned Earlier the !Inevidth Function F(e) Relates \Vsupporting
confidence: 75%
See 2 more Smart Citations
“…We argued in section 2 that changes of the interaction of the CO 5u, a.nd the surface metal d orbitals dominate coordination of CO to Pt. The analysis presented here not only agrees with this, it also predicts that CO binds most strongly atop to the (111) surface (7). Only at lower d-valence electron occupation coordination to the more open surfaces becomes favoured.…”
Section: As Mentioned Earlier the !Inevidth Function F(e) Relates \Vsupporting
confidence: 75%
“…Figures 1 and 2 show 'lrij 's computed according to the Extended Htickel method for a CO molecule atop adsorbed to a 29 atom cluster of Rh atoms simulating the Rh ( 111) surface. For details we refer to (7). Figures 1 present the BOOPD 1fsu,d 2 , 7rsu,s and 7rsu,p· These are the only non-zero BOOPD's of s symmetry.…”
Section: Molecular Orbital Theory Of Co Chemisorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…molecular orbital of CO into a free d orbital of the metal and an electron back-donation from an occupied d orbital of the metal into the unoccupied 2p à antibonding orbital of CO. As discussed by Broden et al [18], the activation energy for dissociation may be related to the degree of population of the 2p à antibonding CO orbital (which weakens the C-O bond). CO dissociation seems to be also facilitated if CO bends towards the surface [19][20][21]. For CO dissociation on rhodium, deKoster et al [19] reported a tilting of the C-O bond, with an angle of about 70°between the C-O axis and the surface normal.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, theoretical examinations of the marked variations in CO coordination geometry observed experimentally between these surfaces, even at zero external field, are relatively sparse. 21 To this end, the present paper reports DFT calculations for CO and NO chemisorption on the four Pt-group ͑111͒ surfacesplatinum, iridium, palladium, and rhodium, as well as on the related hexagonal Ru͑0001͒ surface-for which potentialdependent IRAS data, along with detailed results for the UHV-based interfaces, are available. We undertake a broadbased comparison of the DFT results with the experimental findings, focusing attention on the quantum-chemical factors responsible for the observed variations in the preferred binding site and the vibrational frequencies with the metal surface, chemisorbate, and electrostatic field.…”
Section: Introductionmentioning
confidence: 99%